1996
DOI: 10.1097/00000658-199606000-00006
|View full text |Cite
|
Sign up to set email alerts
|

A Physiologic Approach to Laparoscopic Fundoplication for Gastroesophageal Reflux Disease

Abstract: ObjectiveThe authors examined indications, evaluations, and outcomes after laparoscopic fundoplication in patients with gastroesophageal reflux through this single-institution study. Summary of Background DataLaparoscopic fundoplication has been performed for less than 5 years, yet the early and intermediate results suggest that this operation is safe and equivalent in efficacy to open techniques of antireflux surgery. MethodsOver a 4-year period, 300 patients underwent laparoscopic Nissen fundoplication (252)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
195
1
8

Year Published

1998
1998
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 413 publications
(216 citation statements)
references
References 17 publications
12
195
1
8
Order By: Relevance
“…In future studies, combined axial force recordings and manometry may provide more useful information on esophageal muscle function in basic and clinical studies, especial protocols where a challenge test of the esophagus is incorporated will be of major interest in basic and clinical studies. It has been suggested that manometry could subgroup gastroesophageal reflux disease patients into those requiring partial or total fundoplication treatment [29][30][31] . However, studies have not been able to prove that preoperative manometry could predict postoperative outcome in terms of dysphagia [32][33][34] .…”
Section: Resultsmentioning
confidence: 99%
“…In future studies, combined axial force recordings and manometry may provide more useful information on esophageal muscle function in basic and clinical studies, especial protocols where a challenge test of the esophagus is incorporated will be of major interest in basic and clinical studies. It has been suggested that manometry could subgroup gastroesophageal reflux disease patients into those requiring partial or total fundoplication treatment [29][30][31] . However, studies have not been able to prove that preoperative manometry could predict postoperative outcome in terms of dysphagia [32][33][34] .…”
Section: Resultsmentioning
confidence: 99%
“…Patients (n = 14, 50% female) available at 2 years had a median age of 34 (range, 23-55) years and a median BMI of 22 (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31) kg/m 2 . Patients had suffered from GERD for a median of 10 (range, 3-15) years and were on continuous daily PPI therapy for a median of 6 (range, 2-13) years before undergoing TIF.…”
Section: Patient Characteristicsmentioning
confidence: 99%
“…Hunter and colleagues (103) reported symptomatic improvement in 25 of 30 asthma patients following fundoplication. Unfortunately, neither the effects on asthma medication requirements nor pulmonary function were reported.…”
Section: Effects Of Surgical Antireflux Therapymentioning
confidence: 99%